Assessing 2D electrophoretic mobility spectroscopy (2D MOSY) for analytical applications - Fang, Yuan (Magnetic resonance in chemistry : MRC, 2017)
Copyright © 2016 The Authors. Magnetic Resonance in Chemistry published by John Wiley & Sons Ltd.